2016
DOI: 10.1038/srep33519
|View full text |Cite
|
Sign up to set email alerts
|

Circulating tumor DNA detection in lung cancer patients before and after surgery

Abstract: Circulating tumor DNA (ctDNA) in peripheral blood is a “liquid biopsy” that contains representative tumor information including gene mutations. Additionally, repeated ctDNA samples can be easily obtained to monitor response to treatment and disease progression, which may be especially valuable to lung cancer patients with tumors that cannot be easily biopsied or removed. To investigate the changes in ctDNA after surgical tumor resection, tumor and blood samples obtained before and after surgery were collected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
92
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(103 citation statements)
references
References 39 publications
(45 reference statements)
7
92
0
2
Order By: Relevance
“…As this was not accompanied by increased (or any) ctDNA in most instances, it suggests elevated nonmalignant cell death in the wake of systemic cytotoxic therapy. In pregnant women, fetal cfDNA is cleared rapidly from circulation after childbirth (43), and ctDNA levels reduce after surgery in patients with NSCLC and colorectal cancer (44,45). The same is likely true in patients with bladder cancer responding to chemotherapy.…”
Section: Discussionmentioning
confidence: 98%
“…As this was not accompanied by increased (or any) ctDNA in most instances, it suggests elevated nonmalignant cell death in the wake of systemic cytotoxic therapy. In pregnant women, fetal cfDNA is cleared rapidly from circulation after childbirth (43), and ctDNA levels reduce after surgery in patients with NSCLC and colorectal cancer (44,45). The same is likely true in patients with bladder cancer responding to chemotherapy.…”
Section: Discussionmentioning
confidence: 98%
“…Noninvasive biopsy provides a valuable way to monitor tumor treatment efficacy . As shown in Supporting Information Figure S5A, the amount of unanticipated points became less along treatment course from cfDNA1 to cfDNA3, indicating the overall pattern of cfDNA approached the reference genome, that is, the pattern of WBC, as treatment progressed.…”
Section: Resultsmentioning
confidence: 99%
“…The results of the current study add to the body of evidence accumulating regarding the usefulness of ctDNA as a blood‐based diagnostic test. Although several studies have reported on the ability to detect genetic aberrations in the blood of patients with early‐stage lung cancer, to our knowledge the cohorts usually were small and assessments of clinical test performance were undertaken with respect to FFPE mutations rather than a clinical diagnosis of cancer …”
Section: Discussionmentioning
confidence: 99%
“…Although several studies have reported on the ability to detect genetic aberrations in the blood of patients with early-stage lung cancer, to our knowledge the cohorts usually were small and assessments of clinical test performance were undertaken with respect to FFPE mutations rather than a clinical diagnosis of cancer. 8 The diagnostic clinical test performance invariably varies with the methods used for DNA enrichment and the identification of genetic aberrations. COLD-PCR with high-resolution melt analysis has the advantage of being a readily available, low-cost method for the blood-based detection of cancer-related single-nucleotide variants, but Cancer April 15, 2020…”
Section: Discussionmentioning
confidence: 99%